A porphyrin-based ratiometric SERS sensor for high-throughput and ultrasensitive cadmium ion detection. Issue 36 (18th April 2023) - Wang, Rui; Wu, Shuo; Dong, Yumiao; Xie, Yunfei; Ji, Wei
Abstract : We propose a novel method for sensitive SERS detection of Cd 2+ ions based on TMPyP-triggered Ag aggregates. The response of this sensing system toward Cd 2+ ions could be obtained within 200 s due to the surface plasmon induced photothermal effect. Abstract : We propose a novel method for highly sensitive SERS detection of Cd 2+ ions based on TMPyP-triggered Ag aggregates, which is achieved via a simple electrostatic interaction. In particular, this sensing system is relatively simple, but provides high sensitivity and excellent selectivity in a high-throughput fashion.